2018
DOI: 10.1126/science.aan5951
|View full text |Cite
|
Sign up to set email alerts
|

Genomic correlates of response to immune checkpoint therapies in clear cell renal cell carcinoma

Abstract: Immune checkpoint inhibitors targeting the programmed cell death-1 receptor (PD-1) improve survival in a subset of patients with clear cell renal cell carcinoma (ccRCC). To identify genomic alterations in ccRCC that correlate with response to anti-PD-1 monotherapy, we performed whole exome sequencing of metastatic ccRCC from 35 patients. We found that clinical benefit was associated with loss-of-function mutations in the PBRM1 gene (p=0.012), which encodes a subunit of a SWI/SNF chromatin remodeling complex (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
860
8
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 986 publications
(942 citation statements)
references
References 57 publications
(49 reference statements)
26
860
8
3
Order By: Relevance
“…A study by Miao et al . in this issue demonstrates that PBRM1 mutations in metastatic renal cancers are associated with improved clinical responses to PD-1 or PD-L1 blockade (37). Mutations in ARID2 and BRD7 are also observed in a variety of other human cancers, including ARID2 mutations in melanoma (38).…”
Section: Discussionmentioning
confidence: 99%
“…A study by Miao et al . in this issue demonstrates that PBRM1 mutations in metastatic renal cancers are associated with improved clinical responses to PD-1 or PD-L1 blockade (37). Mutations in ARID2 and BRD7 are also observed in a variety of other human cancers, including ARID2 mutations in melanoma (38).…”
Section: Discussionmentioning
confidence: 99%
“…Although harbouring extremely low burden of immunotherapy-related somatic mutations compared with other tumour types, ccRCC exhibits strong response to immunotherapy, suggesting that it shall undergo a unique and distinctive regulation mechanism or signalling pathway 25–31. In line with this hypothesis, whole exome sequencing analysis have revealed that the loss-of-function mutation in chromatin remodeler polybromo-1 gene is a key factor causing altered immune signalling pathways in patients with metastatic ccRCC 32. Furthermore, expression of major histocompatability complex class I antigen presenting machinery could reflect the prognosis and immunotherapeutic benefits in ccRCC 31.…”
Section: Introductionmentioning
confidence: 91%
“…Current investigations across cancer subtypes are geared toward defining mechanisms that underlie positive and lasting responses to immune checkpoint blockade. A recent study identified signatures of response to checkpoint therapies in ccRCC [111]. Through whole exome sequencing of 35 tumors of patients with metastatic ccRCC, it was determined that biallelic PBRM1 loss was associated with significantly longer overall survival than patients with PBRM1 intact.…”
Section: Therapeutic Strategies For Ccrccmentioning
confidence: 99%